The Role of Persuasive Communication through Positive Affirmations in Enhancing Self-Efficacy of Elementary School Students: An Islamic Educational Psychology Perspective - Marwal Blantara Susetyo; Pitra Gosha Patriasya; Magna Anissa A. Hayudini (WISE Pendidikan Indonesia, 2026)
This study explores the role of persuasive communication through positive affirmations in enhancing the self-efficacy of elementary school students in Desa Cisalak, with a focus on Islamic Educational Psychology. The research uses a qualitative descriptive phenomenological approach to understand the experiences of teachers and students regarding positive affirmations in the classroom. Data were collected through in-depth interviews, participatory observation, and documentation from 14 participants, including 4 teachers and 10 students. The findings show that persuasive communication through positive affirmations plays a significant role in shaping students’ self-efficacy by reinforcing their belief in their abilities and motivating them to engage more actively in learning. Positive affirmations foster a growth mindset, aligning with Islamic principles of self-improvement and trust in Allah’s guidance. However, challenges such as the lack of parental support and peer pressure hinder the effectiveness of affirmations. The research suggests that a supportive ecosystem, involving both school and home, is essential for affirmations to be effective. The study provides practical insights for educators, emphasizing verbal encouragement, positive reinforcement, and creating an environment that nurtures both cognitive and spiritual development in students. This research contributes to the understanding of self-efficacy in Islamic education and offers strategies for enhancing students' academic motivation and personal growth.